Discontented Voters or Populists?: Investigating Populist Attitudes Among the Economic Freedom Fighters’ Supporters - Schwegmann, Tayla Ann (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.